2010
DOI: 10.1002/bjs.7092
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of lower limb amputation in England between 2003 and 2008

Abstract: Major and minor amputation rates were stable across England between 2003 and 2008, accompanied by a significant reduction in perioperative mortality. There were significant geographical variations in amputation rates, mortality rates and the below-knee : above-knee amputation ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
142
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(162 citation statements)
references
References 32 publications
14
142
2
4
Order By: Relevance
“…1-7 A significantly higher mortality rate for AKA (18.4%) than BKA patients (4.5%) is also consistent with previous studies. 2 There are several significant findings in our study. Firstly, pre-operative septic shock, ASA 4 status and site of amputation of AKA are significant predictors of higher post-operative in hospital mortality rate and ICU admission.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…1-7 A significantly higher mortality rate for AKA (18.4%) than BKA patients (4.5%) is also consistent with previous studies. 2 There are several significant findings in our study. Firstly, pre-operative septic shock, ASA 4 status and site of amputation of AKA are significant predictors of higher post-operative in hospital mortality rate and ICU admission.…”
Section: Discussionsupporting
confidence: 54%
“…[1][2][3][4][5][6][7] Patient's pre-operative condition, including their ASA status, presence of septic shock and site of amputation undertaken are significant predictors of post-operative in hospital mortality rate and ICU admission rate. Patients with pre-operative septic shock, ASA 4 status and undergoing AKA should be regarding as high risk group, and appropriate level of intra-operative monitoring and post-operative disposition should be arranged.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In another study, major and minor amputation rates were stable across England between 2003 and 2008, accompanied by a significant reduction in perioperative mortality. 12 Other authors have reported that there was significant reduction in the incidence of major LEA in patients with diabetes over a 7-year period (January 1, 2000 to December 31, 2006). 13 Differences in outcomes have been recorded between patients with PAD versus patients with diabetes and PAD.…”
Section: Advances In the Treatment Of Peripheral Vascular Disease In mentioning
confidence: 91%